Pre-operative external ventricle drainage improves neurological outcomes for patients with traumatic intracerebellar hematomas - Wang, Bao; Gao, Li; Zhang, Yu; Su, Ming-ming; Shi, Wei; Wang, Yue; Ge, Shun-nan; Zhu, Gang; Guo, Hao; Gao, Fei; Shi, Ying-Wu; Cui, Wen-xing; et al. (Frontiers in Neurology, 2022)
Objectives Traumatic intracerebellar hematoma (TICH) is a very rare entity with a high morbidity and mortality rate, and there is no consensus on its optimal surgical management. In particular, whether and when to place external ventricle drainage in TICH patients without acute hydrocephalus pre-operation is still controversial. Methods A single-institutional, retrospective analysis of total of 47 TICH patients with craniectomy hematoma evacuation in a tertiary medical center from January 2009 to October 2020 was performed. Primary outcomes were mortality in hospital and neurological function evaluated by GOS at discharge and 6 months after the ictus. Special attention was paid to the significance of external ventricular drainage (EVD) in TICH patients without acute hydrocephalus on admission. Results Analysis of the clinical characteristics of the TICH patients revealed that the odds of use of EVD were seen in patients with IVH, fourth ventricle compression, and acute hydrocephalus. Placement of EVD at the bedside can significantly improve the GCS score before craniotomy, as well as the neurological score at discharge and 6 months. Compared with the only hematoma evacuation (HE) group, there is a trend that EVD can reduce hospital mortality and decrease the occurrence of delayed hydrocephalus, although the difference is not statistically significant. In addition, EVD can reduce the average NICU stay time, but has no effect on the total length of stay. Moreover, our data showed that EVD did not increase the risk of associated bleeding and intracranial infection. Interestingly, in terms of neurological function at discharge and 6 month after the ictus, even though without acute hydrocephalus on admission, the TICH patients can still benefit from EVD insertion. Conclusion For TICH patients, perioperative EVD is safe and can significantly improve neurological prognosis. Especially for patients whose GCS dropped by more than 2 points before the operation, EVD can significantly improve the patient's GCS score, reduce the risk of herniation, and gain more time for surgical preparation. Even for TICH patients without acute hydrocephalus on admission CT scan, EVD placement still has positive clinical significance.